Linguocultorological reasons for the different levels of somatization of sadness in languages of the world - Eleonora Girina (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
Considering their important role in human life the study of emotions is of great interest for linguistic science. This article is dedicated to the analysis of the phenomenon of somatization of sadness and the explanation of differences in the levels of such somatization as reflected in language.